Anthropogenic carbon in the ocean—Surface to interior connections. Issue 11 (10th November 2016) - Groeskamp, Sjoerd; Lenton, Andrew; Matear, Richard; Sloyan, Bernadette M.; Langlais, Clothilde
Abstract: Quantifying the surface to interior transport of anthropogenic carbon (CA ) is critical for projecting future carbon uptake and for improved understanding of the role of the oceans in the global carbon cycle. Here we develop and apply a diagnostic tool that provides a volumetric stream function in (CA, σ 0 ) coordinates to calculate the total diapycnal CA transport in the ocean, where σ 0 is the surface referenced potential density anomaly. We combine this with air‐sea fluxes of CA to infer the internal ocean mixing of CA to obtain a closed globally integrated budget analyses of the ocean's CA transport. This diagnostic separates the contribution from the mean flow, seasonal cycles, trend, surface fluxes, and mixing in the distribution and the accumulation of CA in the ocean. We find that the redistribution of CA from the surface to the interior of the ocean is due to an interplay between circulation and mixing. The circulation component is dominated by the mean flow; however, effects due to seasonal cycles are significant for the CA redistribution. The two most important pathways for CA subduction are through the transformation of thermocline water (TW) into subantarctic mode water and by transformation of Circumpolar Deep Water (CDW) into lighter Antarctic Intermediate Water. The results suggest that an accurate representation of intermediate and mode water formation, deep water formation, and spatial and temporal distribution of ocean mixing in ocean models is essential to simulate and project the oceanic uptake of CA . Key Points: New diagnostic revealing Anthropogenic Carbon circulation pathways Separated contribution from seasonality, advection, trend, surface fluxes, and mixing Anthropogenic carbon accumulation mainly at interface between SAMW and AAIW